2002
DOI: 10.1523/jneurosci.22-24-10801.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking D5Dopamine Receptors Have Increased Sympathetic Tone and Are Hypertensive

Abstract: Dopamine is an important transmitter in the CNS and PNS, critically regulating numerous neuropsychiatric and physiological functions. These actions of dopamine are mediated by five distinct receptor subtypes. Of these receptors, probably the least understood in terms of physiological functions is the D5 receptor subtype. To better understand the role of the D5 dopamine receptor (DAR) in normal physiology and behavior, we have now used gene-targeting technology to create mice that lack this receptor subtype. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
154
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 47 publications
7
154
1
Order By: Relevance
“…In D 5 receptor null (D 5 À/À ) mice, a high salt diet further increases blood pressure, suggesting that the renal D 5 receptor has an important role in the control of blood pressure by regulating renal sodium chloride transport. 28,35 In the present study, we found that activation of D 5 receptor inhibits Na + -K + ATPase activity in D 5 receptor-transfected HEK293 cells.…”
Section: Quantitative Rt-pcrsupporting
confidence: 57%
See 1 more Smart Citation
“…In D 5 receptor null (D 5 À/À ) mice, a high salt diet further increases blood pressure, suggesting that the renal D 5 receptor has an important role in the control of blood pressure by regulating renal sodium chloride transport. 28,35 In the present study, we found that activation of D 5 receptor inhibits Na + -K + ATPase activity in D 5 receptor-transfected HEK293 cells.…”
Section: Quantitative Rt-pcrsupporting
confidence: 57%
“…28 For b-actin, the forward primer was 5¢-GTGGGTATGGGTCAGAAGGA-3¢ and the reverse primer was 5¢-AGCGCG TAACCCTCATAGAT-3¢. The amplification was performed with the following conditions: 35 cycles of denaturation at 94 1C for 2 min, annealing for 30 s at 52.5 1C and extension for 45 s at 72 1C.…”
Section: Reverse Transcriptase-pcrmentioning
confidence: 99%
“…Immunohistochemical detection of d5 receptors revealed that the frontal cortex in the d5À/À mouse was, as expected, completely devoid of this receptor (Hollon et al, 2002). Animals were reproduced in our animal facilities by standard inbreeding.…”
Section: Methodsmentioning
confidence: 57%
“…The d5À/À mouse with a genetic background of 129/SvJ1 and C57BL/6J was generated as described earlier (Hollon et al, 2002) and provided by one of the authors (D Sibley). Immunohistochemical detection of d5 receptors revealed that the frontal cortex in the d5À/À mouse was, as expected, completely devoid of this receptor (Hollon et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation